Pharmacology of modulators of alternative splicing - Bates, David O.; Morris, Jonathan C.; Oltean, Sebastian; Donaldson, Lucy F. (American Society for Pharmacology and Experimental Therapeutics, 2017)
More than 95% of genes in the human genome are alternatively spliced to form multiple transcripts, often encoding proteins with differing or opposing function. The control of alternative splicing is now being elucidated, and with this comes the opportunity to develop modulators of alternative splicing that can control cellular function. A number of approaches have been taken to develop compounds that can experimentally, and sometimes clinically, affect splicing control resulting in potential novel therapeutics. Here we develop the concepts that targeting alternative splicing can result in relatively specific pathway inhibitors/activators that result in dampening down of physiological or pathological processes, from changes in muscle physiology, to altering angiogenesis or pain. The targets and pharmacology of some of the current inhibitors/activators of alternative splicing are demonstrated and future directions discussed.